(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Personal hygiene is the maintenance and care of the cleanliness of all body parts, including the reproductive organs. During menstruation, blood vessels in the uterus are easily injured. Therefore, personal hygiene is crucial to prevent reproductive organ dysfunction. This study aims to analyze the relationship between knowledge levels and reproductive health behaviors among female students at the Al-Fakhriyah Baturaja Islamic Boarding School. This study used a quantitative method with a cross-sectional design. The study population was 52 female students of the 10th and 11th grades at the Al-Fakhriyah Baturaja Islamic Boarding School. They were selected using accidental sampling, a non-probability sampling technique in which researchers select subjects or respondents based on their ease of access and availability at the time of the study. The research instrument was a questionnaire on personal hygiene knowledge and attitudes toward personal hygiene. Univariate and bivariate data analysis used the chi-square test. The results showed that the majority of female students had good knowledge (40.0%), moderate (44.2%), and poor (15.4%). Positive attitudes (55.8%) and negative attitudes (44.2%). The correlation test showed a significant relationship between female students’ knowledge of personal hygiene and genital hygiene during menstruation (p=0.003), and a significant relationship between female students’ attitudes and knowledge of personal hygiene and genital hygiene during menstruation (p=0.008).